Why are the Barriers into the Labour Market rising? An Analysis of the Exclusion process of Immigrants in the Swedish Labour Market - Backlund, Ann-Katrin (Two Homelands, 2002)
Differences in the degree of unemployment among the native and the immigrated population are characteristic for the whole Europe. Particularly big are those differences in Sweden. The presented results are the product of two researches of posts that by tradition employed a large number of less qualified immigrants, and where decrease is noted. It is presumed that the causes for such exclusion from work can be sought in technological and organisational changes of those works. Those changes were in Sweden carried out faster and more thorough than in other states of the European Union. The standpoints and values, which are rounded up in the term “The Swedish model of a working life” became the strategy for systematic excluding of working potentials of the immigrants.